(untitled) (Journal of Engineering, 2010)
The verse (35) in SURA (AL- Nur) in the HOLY QURAN has inspired the author to look into the possibility of using Olive Oil as active dye laser material. Olive Oil which is classified as organic compound, having a good properties candidate it to be used as active dye laser material. The emission spectrum diagrams at some of absorption peaks (414, 536, 632 and 670) nm will be measured. These diagrams have been used to determine the Fluorescence quantum yield, Oscillator strength, Einstein coefficients for the spontaneous emission, Radiative and Fluorescence lifetime and absorption and cross sections. It has been found that fluorescence occurs at 669 nm for the entire absorption spectrum. Fluorescence of Olive Oil has been experimented using 30mW, 532nm semiconductor laser, with a beam diameter of 1.3mm. Red fluorescence has been noticed over a distance of 7cm in a glass container.